Fauna edáfica associada a solos com diferentes cultivos e sistemas de manejo - Martins , Claudecir Castilho (2020)
This work aimed to evaluate the edaphic fauna associated with soils with different crops and management systems, in field in the agroecological area of the Unioeste experimental station, located in Entre Rios do Oeste - PR. For that, organisms present in soil samples and pitfall traps were quantified. Six samplings were carried out, with 120-day intervals, starting in March 2017 and ending in November 2018. In the samplings the soil collection was carried out in 10 random points per field and 10 Pitfall traps were installed in the places where they were soil samples taken. The samples were taken to the Unioeste Biological Control Laboratory, sorted, labeled and stored separately by collection and field. Then the specimens were quantified and identified with the aid of a stereomicroscope and specific literature. According to the data obtained in the present study, it can be concluded that the largest number of individuals collected was from the Formicidae Family. The Collembola Class, showed uniform distribution among all fields. The rainfall interfered in the indexes of wealth and diversity, which were higher for the collections in the month of July 2018. The interactions between edaphic fauna, soil, climate, vegetation cover and management system, didn’t allow to establish a standard in the analysis of the results of the wealth and diversity indexes, when analyzed by collection. Cluster analysis showed that the management system influences the edaphic community, bringing together places that adopt organic systems.